Рекламний синтез туристичної діяльності - Климко, І. Г.; Климко, И. Г.; Кlimkо, I. G. (My University, 2017)
Стаття присвячена актуальній проблемі рекламних комунікацій у туризмі, що здійснюють інформативно-гармонізуючи та креативні функції, орієнтовані на специфіку туристичної діяльності. Реклама набуває ознак мистецтва як вміння, майстерності, творчості та специфічної прагматики, яка переводить мистецтво у ранг естетичної реальності, що стає співмірною туристичному бізнесу. Реклама як мистецтво, як комунікативна діяльність, певний синтез культурних практик несе у собі розмаїття обслуговуючих її сфер діяльності – графічний дизайн, логодизайн, система презентацій інформації. Рекламна інформація перетворюється у своєрідний видовищний симбіоз, який має свою режисуру, програму формування спільнот споживачів тощо. Реклама функціонує на правах диференційних розгалужених систем рекламної комунікації, таких, як брендинг, паблік рілейшинз. У статті визначаються синтезуючі виміри реклами, починаючи з її комунікативного семантичного універсуму і закінчуючи специфічними визначеннями у просторі туристичної діяльності.

Рекламные коммуникации в туризме осуществляют информативно-гармонизирующие и креативные функции, ориентированные на специфику туристической деятельности. Реклама приобретает признаки искусства как умение, мастерство, творчество, ту специфическую прагматику, которая переводит искусство рекламного воздействия в ранг эстетической реальности, которая становится соизмеримой туристическому бизнесу. Реклама как искусство, как коммуникативная деятельность, как определенный синтез культурных практик несет в себе разнообразие обслуживающих ее сфер деятельности, таких как графический дизайн, логодизайн, система презентаций информации. Рекламная информация превращается в своеобразный зрелищный симбиоз, который имеет режиссуру, программу формирования сообществ потребителей. В статье анализируются синтезирующие начала рекламы, начиная с ее коммуникативного семантического универсума и заканчивая специфическими определениями, собственно в пространстве туристической деятельности.

The article is sanctified to the issue of the day of advertising communications in tourism, that carry out the informing-harmonizing and creative functions oriented to the specific of tourist activity. An advertisement gets symptom as ability, trade, work and specific pragmatics, that transfers an art in the grade of aesthetic reality that becomes commensurable to the tourist business and art. Advertisement as an art, as communicative activity, the certain synthesis of cultural practices carries in itself diersity of attendant her spheres of activity is a graphic design, logodesign, system of presentations of information. Advertising information grows into original spectacle symbiosis that has the direction, program of forming of associations of cjnsumers and others like that. An advertisement functions on rights for the differential ramified systems of advertising communication, such as branding, public relations. The synthesizing measuring of advertisement is determined in the article, beginning from her communicative semantic universum and ending specific determinations in space of tourist activity. Actional measuring – it actually an action at the trip of all agencies as substructures that serve a trip, and also activity of recipient, tourist. It is all space of a goal setting and goal realization as certain megaproject of tourism. Realization of this project all cultural practices of tourist activity engage in. The system of facilities, that carries out goal setting and goal realization tour project comes forward as a combining factor. These facilities present a communicative-informing environment, which helps to unite a project, model, forecasting aspects that are related to marketing and management in tourism. Socioprogmatics of communicative space of tourism – it the measuring, from one side, carries in itself utilization of the codes of culture, related to the road, trip (codes of leaving, maintenances of status of that, who went out from home, to status of guest and others like that), and from other – orientation on a consumer. This semantic and cultural space requires the comprehension in the context of the road’s discourse, comprehension of the road as metanarative, systems of connectad discourses, advertising and other reports.
Климко І. Г. Рекламний синтез туристичної діяльності / І. Г. Климко // Актуальні проблеми філософії та соціології: Науково-практичний журнал / Голов. ред. Д. В. Яковлев; відпов. секретар І. В. Шамша; Міністерство освіти і науки України; Національний університет "Одеська юридична академія". - Одеса, 2017. - Вип. 18. - С. 59-61.
Keywords: культура; туризм; реклама; рекламні комунікації; видовище; синтез мистецтв; культура; туризм; реклама; рекламные коммуникации; зрелище; синтез искусств; culture; tourism; advertisement; advertising communications; spectacle; synthesis of arts